Effects of extreme high flow events on macroinvertebrate communities in Vermont streams. (9th September 2020) - Stamp, Jen; Moore, Aaron; Fiske, Steve; Gerritsen, Jeroen; Bierwagen, Britta; Hamilton, Anna
Abstract: Heavy precipitation events and subsequent high flows are occurring with greater frequency and intensity, which could have substantial implications for biomonitoring programs that typically evaluate changes in biological condition due to stressors at local and watershed scales. In this study we evaluated response and recovery of macroinvertebrate communities at nine reference quality streams located in multiple watersheds throughout Vermont to flooding from Tropical Storm (TS) Irene in 2011. At each site, the Vermont Department of Environmental Conservation (VT DEC) had collected macroinvertebrate data on an annual basis from 2009–2013. We compared the data collected in the days and weeks following TS Irene (2011) to samples collected for 2 years prior to the event (2009–2010) and 2 years after (2012–2013). While most metrics used in Vermont's biocriteria did not demonstrate a response to TS Irene, density showed a significant reduction in 2011 (across sites, percent change ranged from −24 to −91%; mean −66%). The percent change in density at each site was significantly correlated with the amount of localized rainfall during the storm ( r s = −0.79, p = .02) and was most evident at small to medium‐sized, high gradient streams. Reduced density caused several of these sites to fail to meet minimum criteria for biological integrity, though densities rebounded the following year. While the quick recovery indicated resiliency at these reference streams, the timing and magnitude of flood events may decrease the ability of biomonitoring programs to accurately evaluate the effect of watershed stressors.